On the Relationship Between Grammaticalization and Reanalysis - Jarad, Najib (Studia Anglica Posnaniensia, 2011)
This paper seeks to explain and exemplify the relationship between grammaticalization and reanalysis, two important processes of grammatical change which occur in language. The ultimate goal of this paper is to prove that whilst the two are crucially related, they are not mutually dependent and can extensively occur alone. The paper focuses on the shift of for from the thematic function and/or case realizer to the modern pure complementizer status.